PENGEMBANGAN FINANCIAL MODELLING FRAMEWORK (FMF) TERINTEGRASI: PENDEKATAN DESIGN-BASED DALAM ARSITEKTUR MODEL KEUANGAN KORPORASI - Rahardjo, Iman Sjamsu (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
Corporate financial modeling practices have evolved technically, yet they remain largely ad hoc, architecturally undocumented, and insufficiently aligned with governance and model risk principles. Spreadsheet-based models are frequently constructed in a fragmented manner, exposing organizations to assumption inconsistencies and model risk vulnerabilities. This study develops an integrated Financial Modeling Framework (FMF) using a design-based research approach to bridge the gap between financial modeling practice, financial statement analysis, and risk governance principles. The research produces a layered architectural artifact consisting of an assumptions layer, integrated financial statements layer, performance output layer, and validation mechanism. The novelty of this study lies in conceptualizing financial modeling as a governance-aware decision infrastructure that explicitly integrates financial statement structures, ratio transmission logic, and validation controls within a modular and transparent design. Theoretically, the study extends design science applications into the financial domain by emphasizing architectural structuring as a determinant of model quality. Practically, the FMF enhances transparency, consistency, and accountability in spreadsheet-based corporate financial model development.